2011
DOI: 10.1111/j.1752-1688.2011.00600.x
|View full text |Cite
|
Sign up to set email alerts
|

Decentralized Groundwater Recharge Systems Using Roofwater and Stormwater Runoff1

Abstract: Stormwater capture for groundwater recharge in urban areas is usually conducted at the regional level by water agencies. Field and modeling studies in New Mexico indicate that stormwater diverted to retention basins may recharge about 50% of precipitation that falls on the developed area, even in dry climates. Comparable volumes of recharge may be expected at homes, subdivisions, or commercial properties with low-impact development (LID) technologies for stormwater control that promote recharge over evapotrans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 9 publications
0
25
0
Order By: Relevance
“…Additionally, implementing LID technologies creates green spaces, which reduce heat stress mortality, and increase property value and recreational opportunities [11,12]. Rainwater harvesting technology converts stormwater runoff into a water resource, which can be used for groundwater recharge and nonpotable purposes such as irrigation, toilet flushing, and laundry [13][14][15][16][17]. Farreny et al (2011) analyzed the cost-benefit of four rooftop rainwater harvesting strategies in new or retrofit construction for: (1) residential neighborhoods of singlefamily homes, and (2) multi-story buildings [18].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, implementing LID technologies creates green spaces, which reduce heat stress mortality, and increase property value and recreational opportunities [11,12]. Rainwater harvesting technology converts stormwater runoff into a water resource, which can be used for groundwater recharge and nonpotable purposes such as irrigation, toilet flushing, and laundry [13][14][15][16][17]. Farreny et al (2011) analyzed the cost-benefit of four rooftop rainwater harvesting strategies in new or retrofit construction for: (1) residential neighborhoods of singlefamily homes, and (2) multi-story buildings [18].…”
Section: Introductionmentioning
confidence: 99%
“…Observed decreases in groundwater recharge or base flow with urban development have been attributed to factors such as reduced infiltration due to connected impervious surfaces [ Ku et al ., ; Konrad et al ., ; Hardison et al ., ], increased groundwater withdrawals [ Roach et al ., ], export of locally supplied water to wastewater treatment plants [ Pluhowski and Spinello , ; Simmons and Reynolds , ], or infiltration of groundwater into wastewater collection systems. Other studies have observed increases in groundwater recharge or base flow with urbanization that is credited to water supply pipe leakage [ Lerner , ], reduced evapotranspiration, focused recharge of storm water infiltration [ Ku et al ., ; Appleyard , ; Stephens et al ., ; Hogan et al ., ], recovery from industrial groundwater pumping [ VĂĄzquez‐Suñé et al ., ], or discharge of wastewater from imported or confined water supply [ Burns et al ., ; Townsend‐Small et al ., ]. Where a range of these features was present and the increases and decreases nearly balanced out, or the effects on urban development were small compared to predevelopment recharge, little effect was observed from urban development on groundwater recharge or base flow [ Ferguson and Suckling , ; Barringer et al ., ; Yang et al ., ; Kim et al ., ; Trowsdale and Lerner , ; Brandes et al ., ; Meyer , ; Roy et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…LID collects runoff close to the source in small structures, generally in urban areas. While costs can be modest, individual LID projects infiltrate relatively little:~10 3 m 3 /yr (~1 ac-ft/yr) (Stephens et al, 2012;Grebel et al, 2013;Newcomer et al, 2014;Bhaskar et al, 2016;Chen et al, 2016). Regional spreading grounds infiltrate excess surface and/or recycled water from large regions, collecting and routing water with dams and other large infrastructure.…”
Section: Introductionmentioning
confidence: 99%